Implementasi Kebijakan Pendidikan Agama Di Sekolah-Sekolah Katolik: Studi Kasus Kota Blitar Provinsi Jawa Timur - Nurudin Nurudin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2013)
The key issues in this study include: Has there been any violation in the implementation of religious education in Catholic schools? Are the sanctions by the Ministry of Religious Affairs in accordnce with appropriate mechanisms and procedures? What is the local government response in following recommended sanctions by the Ministry of Religious? What individual, social and political consequences/implications from such violation in the implementation of religious education at schools? While the purpose of the study is, firstly, to obtain accurate data and information on issues related to religious education in Catholic schools in Blitar; secondly, to verify the proposed closure of Catholic schools by Blitar Municipal Ministry of Religious Affairs; thirdly, to explore various possible religious, social, political, and security consequences in the community. This study uses qualitative method, from which the results can be described as follows: (1). Based on the applicable laws and regulations, obviously there has been a violation in the implementation of religious education at Catholic schools. (2) Sanctions from the Ministry of Religious Affairs have been found to conform the mechanisms and procedures, from the socialization, training, coordination, to sanctioning stages. (3). No follow up actions have been made by the local government with respect to recommended sanctions by the Ministry of Religious Affairs upon varied considerations (of social, political, and security). (4). Drown-out resolution to the continuing violations of religious education in schools would potentially disturb religious harmony and tend to harm the community to a greater extent.Â Permasalahan dalam penelitian ini adalah apakah terjadi pelanggaran dalam pelaksanaan pendidikan agama di sekolah-sekolah Katolik? Apakah pemberian sanksi yang diberikan oleh Kementerian Agama telah sesuai dengan mekanisme dan prosedur? Bagaimana respon Pemerintah daerah dalam menindaklanjuti rekomendasi pemberian sanksi oleh Kementerian Agama? Bagaimana konsekuensi/implikasi individual, sosial dan politik terhadap pelanggaran pelaksanaan pendidikan agama di sekolah?. Sedangkan tujuan penelitian adalah Pertama, memperoleh data dan informasi yang akurat tentang persoalan yang terkait pendidikan agama di sekolah-sekolah Katolik kota Blitar, Kedua, verifikasi terhadap usulan penutupan sekolah-sekolah Katolik oleh Kementerian Agama kota Blitar, Ketiga, mendalami berbagai kemungkinan dampak keagamaan, sosial, politik, dan keamanan pada masyarakat. Penelitian ini menggunakan metode kualitatif. Adapun hasil penelitiannya adalah (1). Berdasarkan peraturan dan perundangan yang berlaku, secara nyata telah terjadi pelanggaran dalam pelaksanaan pendidikan agama di sekolah-sekolah Katolik. (2). Prosedur pemberian sanksi yang diberikan oleh Kementerian Agama telah sesuai dengan mekanisme dan prosedur, yaitu dimulai tahap sosialisasi, pembinaan, koordinasi, dan pemberian sanksi. (3). Pemerintah daerah belum menindaklanjuti dengan memberikan sanksi atas rekomendasi Kementerian Agama dengan berbagai pertimbangan (sosial, politik, dan keamanan). (4). Penyelesaian yang berlarut terhadap pelanggaran pelaksanaan pendidikan agama di sekolah akan berpotensi mengganggu kerukunan umat beragama dan cenderung merugikan masyarakat yang lebih luas.